AI and the future of human-centered education - Kraaijenbrink, Ranco (Acta Herediana, 2026)
This case study investigates pedagogical innovation to re-emphasize human capabilities within AI's disruption, aiming to avoid the "AI trap." It focuses on a redesigned Leadership and Sustainability course for business students (typically 20-25 students per cohort) at Del Rosario University, Bogota, Colombia. The methodology uses an experiential learning model around the "Conscious Capitalism carbon fiber bikes" business simulator as an ongoing case study. This approach integrates David A. Kolb's Experiential Learning Theory, brain-based learning principles, and aspects of the flipped classroom model, redefining the teacher's role as a coach of the learning process. Main findings demonstrate that this immersive "learn-by-doing" approach fosters teamwork, strategic decision-making, and impact analysis—skills that are difficult to acquire through traditional methods. For instance, balanced scorecard data consistently showed improved market share and reputation metrics, e.g., average market share increasing by 15%, across most teams by the final rounds, alongside qualitative evidence from reflections detailing enhanced collaborative problem-solving. The simulator, by using tension and emotions, improves retention in line with brain-based learning. This student-driven environment promotes self-paced learning, mindfulness, and high engagement, while also promoting critical thinking, self-management, and problem-solving. It shows a human-centered integration of technology, where the simulator facilitates active experimentation without replacing core cognitive functions. To summarize, this teaching strategy effectively prevents the "AI trap," training students to handle complexity by developing unique human capacities.